Substance evolution and wear mechanism on friction contact area of brake disc for high-speed railway trains at high temperature. (April 2020) - Zhang, Peng; Zhang, Lin; Wei, Dongbin; Wu, Peifang; Cao, Jingwu; Shijia, Cairang; Qu, Xuanhui
Highlights: The structure of tribo-film was elucidated at temperatures ranging from 400 to 800 ℃. The transformation of wear mechanism with the increased temperature was revealed. The close relationship between friction performance and tribo-film was provided. Abstract: The high temperature induced by the increased braking speed of high-speed railway train leads to the variation of structure and composition of tribo-film on the wear region of brake disc. The tribo-film was characterized in detail after the pin-on-disc experiments at 400–800 ℃. The results indicate with the increase of temperature, the tribo-film changes from single layer structure (mechanical mixing layer (MML)) to double layer structure (MML at the bottom and oxide layer at the top). In addition, the wear mechanism also changes from abrasive wear on the surface of disc to adhesive wear on the tribo-film. Those are related to the increased substance transfer rate between the friction interfaces with the softening of copper matrix.